O-021 Significant improvement in patient functional outcome after revascularization of the middle cerebral artery by mechanical thrombectomy. (16th November 2010) - Frei, D; Bellon, R; Kulcsar, Z; Bonvin, C; Rufenacht, D; Alfke, K; Stingele, R; Jansen, O; Madison, M; Struffert, T; Dörfler, A; Grunwald, I; et al.
Abstract : Purpose: The extent to which acute ischemic stroke patients' functional outcome can be improved by mechanical thrombectomy remains controversial. This is due in part to the lack of appropriate control groups in trials with these devices. The purpose of this study was to assess the effect of the novel mechanical thrombectomy device, the Penumbra System, on patient 90 day outcome and compare the results with an appropriate control group from peer reviewed literature. Methods and materials: This study was a retrospective case review of 89 consecutive patients at seven international centers with occlusion of the middle cerebral artery (MCA) who were treated with the Penumbra System. All patients reviewed presented to the hospital within 8 h of symptom onset with a treatable MCA occlusion (TIMI 0 or 1). The primary end point was good functional outcome, as defined by a modified Rankin Scale (mRS) score of 2 or less at 90 days postprocedure. Published results from the placebo patients in the PROACT II trial were used as the historical control. Results: Mean baseline values at enrollment were: age 66 years, median National Institutes of Health Stroke Scale (NIHSS) score 15 (range 5–25), 51% were females and the median time from symptom onset to arterial puncture was 4.5 h. After use of the Penumbra System, 88% of the treated vessels were revascularized to TIMI 2 or 3. At discharge, 37% of patients had an NIHSS score of 0–1 or an improvement of at least 10 points. Six procedural serious adverse effects were reported in 89 patients (7%). There were a total of five (6%) symptomatic intracerebral haemorrhages reported at 24 h. At 90 days, all cause mortality was 15%. Of the 70 patients who either died or reached the 90 day follow-up, 36 (51%) had mRS scores of ≥2. Abstract O-021 table 1 shows the comparisons with the placebo patients from the PROACT II trial ( JAMA 1999;282 :2003–11). Conclusions: These results suggest that when an appropriate group is used as the control, successful revascularization by the Penumbra System is associated with better functional outcome and survival.